Effectiveness of Different Distraction Techniques in The Management of Anxiety in Differently Abled Pediatric Dental Patients - A Randomized Comparative Clinical Study: Life Sciences-Health - CH, Arun Kanth; Silas, Arun Jacob; Guruswamy, Kayalvizhi; Sajeev, R; A, Sanguida (International Journal of Life Science and Pharma Research, 2022)
Anxiety and fear have become the most significant problem for normal children and differently-abled children at the dental operatory. Various techniques in distraction such as audio, and visual are employed for the behavior management of children. The study aimed to evaluate the effectiveness of four different techniques in anxiety management in differently abled dental pediatric patients. The study included 120 children, randomly assorted into four groups i.e consisting of 30 children in each. Each of these groups was subjected to different distraction techniques, like audio distraction, audio-visual distraction, video distraction and tell-show-do techniques. The parameters assessed were systolic and diastolic blood pressure (SBP and DBP), pulse rate (PR) and oxygen saturation (SPO2) levels. Variables were compared before, during and after the dental procedure using Kruskal-Wallis test. Post-hoc analysis and Bonferroni tests were used to determine the statistical significance in inter-group comparison. SBP was insignificant statistically intra-group at before-after time points. However, SBP during-after treatment showed statistical significance in intergroup (p=0.02). SBP in audio-visual distraction was statistically significant when compared with video distraction group. There was no statistically significant difference observed in the DBP and PR for intra and intergroup, however, SPO2 levels at alltime points in intergroup were statistically significant (p<0.001). Audio-visual distraction proved to be effective as a part of the behavior management technique followed by audio distraction. These non-pharmacological behavior management techniques provided a peaceful dental environment for differently abled children, who have anxiety and fear.